ENHANCED RBAC DENGAN PENDEKATAN HIERARCHICAL DAN DOCUMENT LIFECYCLE PADA SISTEM MANAJEMEN DOKUMEN - Wildan Jazuli; Zaenuddin Zaenuddin; Mochamad Budi Susanto (Jurnal Komputer dan Teknologi, 2026)
Access rights management in Document Management Systems (DMS) has become a critical challenge in organizations with complex and dynamic structures. Conventional Role-Based Access Control (RBAC) models have limitations in addressing access requirements that consider organizational hierarchy and changes in document status throughout its lifecycle. This study proposes an Enhanced RBAC model by integrating hierarchical roles and document lifecycle as a more adaptive and context-aware access control mechanism. The research method employs a prototyping approach with iterative development, along with quantitative evaluation through access scenario testing, performance measurement, and business process efficiency analysis. The evaluation is conducted using multiple scenarios representing various combinations of roles, hierarchical structures, and document states. The results indicate that the proposed model is able to reduce unauthorized access across all testing scenarios, improve approval process efficiency by 35%, and minimize access errors during testing. The main contribution of this study lies in the integration of hierarchical organizational structures and document states into the RBAC model, resulting in a more flexible, adaptive, and effective access control mechanism that meets the requirements of modern document management systems.